Development of an active site titration reagent for α-amylases. Issue 2 (11th November 2020) - Sweeney, Ryan P.; Danby, Phillip M.; Geissner, Andreas; Karimi, Ryan; Brask, Jesper; Withers, Stephen G.
Abstract : α-Amylases are among the most widely used classes of enzymes in industry and considerable effort has gone into optimising their activities. Abstract : α-Amylases are among the most widely used classes of enzymes in industry and considerable effort has gone into optimising their activities. Efforts to find better amylase mutants, such as through high-throughput screening, would be greatly aided by access to precise and robust active site titrating agents for quantitation of active mutants in crude cell lysates. While active site titration reagents designed for retaining β-glycosidases quantify these enzymes down to nanomolar levels, convenient titrants for α-glycosidases are not available. We designed such a reagent by incorporating a highly reactive fluorogenic leaving group onto unsaturated cyclitol ethers, which have been recently shown to act as slow substrates for retaining glycosidases that operate via a covalent 'glycosyl'-enzyme intermediate. By appending this warhead onto the appropriate oligosaccharide, we developed efficient active site titration reagents for α-amylases that effect quantitation down to low nanomolar levels.